Influence of the application of the G050 norm in the safety climate of the construction works of the Surquillo district - Del Águila Guerrero, Edson F. (2020)
The purpose of this research is to study the relationship between the application of the G050 standard (independent variable) and the safety climate of construction works in the Surquillo district (dependent variable). The methodology used corresponds to the type of applied research, evaluative level, with a non-experimental design (ex post-facto). The study population is the workers of 25 multifamily construction works in the Surquillo district, and the sample was 196 workers chosen through simple random sampling. The investigation showed that the application of the G050 standard influences the Safety Climate of the Construction Works of the Surquillo District in that the general averages of the independent and dependent variable exceed the expected central value, therefore representing positive values; also, from the hypothesis test a dependency relation of the variable V2 with respect to variable V1 was demonstrated; therefore, companies in the construction sector should consider these variables in their comprehensive management of OSH in order to ensure effective loss prevention.